1998
DOI: 10.1007/s001980050048
|View full text |Cite
|
Sign up to set email alerts
|

Colles' Fracture of the Wrist as an Indicator of Underlying Osteoporosis in Postmenopausal Women: A Prospective Study of Bone Mineral Density and Bone Turnover Rate

Abstract: Colles' fracture has been shown to be associated with an increased risk of hip fracture. The incidence of low bone mineral density (BMD) and high bone turnover in such patients is uncertain. The aim of this study was to prospectively assess BMD and bone turnover in a cohort of consecutive postmenopausal Colles' fracture patients. BMD (spine, hip and contralateral radius) was measured by dual-energy X-ray absorptiometry (DXA) within 2 weeks of fracture. Bone turnover was assessed within 4 days by measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
86
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(99 citation statements)
references
References 21 publications
8
86
1
3
Order By: Relevance
“…It has been observed that women aged b66 years with wrist fracture have considerably low BMD in the hip. 26 The results of the current study are supported by Eftekhar-Sadat et al, 27 who evaluated the role of wrist BMD in diagnosing osteoporosis in postmenopausal women. BMD measurements revealed osteopenia and osteoporosis in the wrist in 40.4% and 59.6% of participants, in the hip in 38.4% and 24.2% of participants, and in the lumbar spine in 36.4% and 49.5% of participants.…”
Section: Discussionsupporting
confidence: 78%
“…It has been observed that women aged b66 years with wrist fracture have considerably low BMD in the hip. 26 The results of the current study are supported by Eftekhar-Sadat et al, 27 who evaluated the role of wrist BMD in diagnosing osteoporosis in postmenopausal women. BMD measurements revealed osteopenia and osteoporosis in the wrist in 40.4% and 59.6% of participants, in the hip in 38.4% and 24.2% of participants, and in the lumbar spine in 36.4% and 49.5% of participants.…”
Section: Discussionsupporting
confidence: 78%
“…In two previous studies, a significantly higher prevalence of osteoporosis in women with distal forearm fracture compared with age-matched women without fracture was found only among those aged 65 years or younger [6,7]. Results of such comparisons could be influenced in different studies by factors such as the size of the fracture cohort, participation rate, age ranges included, sites measured, or type of control cohorts (normative population or agematched women with no fracture).…”
Section: Discussionmentioning
confidence: 96%
“…In an English cohort of 106 women, mean age 66 (37-89) years, the prevalence of osteoporosis was 21% (spine), 42% (hip), and 50% (either site) [6], and in a Spanish cohort of 58 women, mean age 66 (45-80) years, the prevalence was 47% (spine) and 19% (hip) [7]. In a Dutch cohort of 94 women, mean age 69 (55-79) years, osteoporosis prevalence (spine or hip) was 51% [8], and in an Irish cohort of 100 women, mean age 68 (60-86) years, it was 68% [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wrist fracture (WF) is one of the most common forms of osteoporotic fractures and can help predict subsequent vertebral and hip fractures (Owen et al 1982;Earnshaw et al 1998;Cuddihy et al 1999). The lifetime incidence of WF is generally about 16% in white women.…”
Section: Introductionmentioning
confidence: 99%